EVALUASI PELAKSANAAN PROGRAM INKLUSI SEKOLAH DASAR - Widyawati, Rika (Universitas Kristen Satya Wacana, 2017)
This study aimed to evaluate the implementation of inclusive program in Public Elementary School 2 Klero (SD Negeri 2 Klero), Tengaran, Semarang. This study is an evaluation research with descriptive qualitative approach with CIPP model. The data source consisted of teachers, headmaster, and school committee. The data were collected through interview, observation and documentation. The results of this study: on Context evaluation showed that the school already has got the permission as well as the guidance in order to implement the inclusive program; on Input evaluation showed that the special infrastructures were inadequate, the curriculum had already been modified, special trainings had not been spread evenly, and there was no special assistant in school; on Process evaluation showed that the results of teachersâ competency were acceptable in dealing with children with special needs, individual treatment, but BOS fund is the only financial support and there was no continual monitoring from government; and on Product evaluation the result showed that the academic and non academic achievements of children with special needs were average.